Biochemical and nutritional profile of maize bran‐enriched flour in relation to its end‐use quality. Issue 6 (4th May 2021) - Hussain, Muzzamal; Saeed, Farhan; Niaz, Bushra; Afzaal, Muhammad; Ikram, Ali; Hussain, Shahzad; Mohamed, Abdellatif A.; Alamri, Mohamed S.; Anjum, Faqir M.
Abstract: The core objective of current research was determined to nutritional and bioactive profile of maize bran (MB)‐enriched flour in relation to its end‐use product quality. Furthermore, rheological properties of MB‐enriched flour at different levels (5%, 10%, and 15%) were explicated through farinograph and mixograph. Moreover, bread was prepared with the addition of MB‐enriched flour and was characterized for nutritional and textural properties. Results showed that MB‐enriched flour having high water absorption and water retaining potential up to 4%–7% as compared to wheat flour (WF). Moreover, dough height gradually decreased with the addition of MB due to water‐binding ability of bran which causes a decrease in gas retention during fermentation. This resulted in bread volume decrease (4%–7%) as compared to WF. Furthermore, the moisture content and hardness increased with the addition of MB. The water activity of bread slightly increased with the addition of maize bran after 4‐day storage. Conclusively, MB‐enriched flour improved nutritional, textural, and sensorial properties of final product. Abstract : Maize bran‐enriched flour is rich source of nutritional and bioactive components. Maize bran‐enriched flour bread has high dietary fibers than wheat flour bread. MB‐enriched flour bread explicated high score of sensorial overall acceptability.